KAJIAN ANGKUTAN UDARA PERINTIS KARGO DI PROPINSI PAPUA - Dina Yuliana; Sitti Subekti; Dedes Kusumawati; Mohammad Alwi; Sri Windrasari; Tito Yusmar; Tangkas Janris; Tri Nusiogo (Research and Development Agency of The Ministry of Transportation, 2018)
High logistics costs which may cause the price gap (disparity) between regions in Indonesia. The high cost of logistics in Papua is also caused by the topography of the area which is largely mountainous region so that the accessibility of people and goods will be very dependent on air transport. Air transport facilities and infrastructure in Papua are still inadequate. Purposes of the study is to investigate the mechanisms of implementation and monitoring subsidies pioneering air transport of cargo to optimize the cost of air freight pioneer in Papua Province. With the ever descriptive qualitative research methods. Based on the analysis and discussion of the Air Transport Pilot Study Implementation of Cargo in Papua it can be concluded the following matters: mplementation of pioneering air transport of cargo is required to reduce the price gap between regions in the district capital of Papua (Timika, Wamena and Yakuhimo) to the surrounding districts. Of the several routes proposed by local government district in Papua, there are 11 routes that should be a priority in the implementation of pioneering air transport of cargo, ie: Timika-Beoga, Timika-Ilaga, Timika-Sinak, Timika-Kenyam, Wamena-Mugi, Wamena-Mamit, Wamena-Mapenduma, Dekai-Silimo, Dekai-Anggruk, Dekai-Korupun dan Dekai-Ubahak. Results of calculations and estimates of the type of aircraft and payload in the district of papua, it was concluded that the aircraft type DHC-6, C208B and PILATUS PC6, with a carrying capacity / payload of 800 kg / flight - 1000 kg /flight.